Learning occupational safety through gamification: A randomized controlled field trial - La Torre, Giuseppe; Capece, Guendalina; Shaholli, David; Nicolì, Francesca; Mannocci, Alice (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background. Traditional health and safety training often fail to engage workers effectively. Gamification has emerged as a promising strategy to enhance motivation and learning outcomes. This study aimed to assess the effectiveness of a gamified training course in improving occupational health and safety knowledge.Methods. A randomized controlled field trial was conducted with 77 participants. Participants were divided into two groups: an experimental group (EG) and a control group (CG). The intervention, titled “Let's play to 626!” consists of a one-day course comprising a seminar and gaming session. The participants were assessed using an internally validated Q626 questionnaire at baseline (T0) and after the intervention (T1), with a knowledge score was computed ranged from to 0-15. Descriptive statistics, paired sample tests, and regression analyses were used to analyse the data.Results: The internal reliability of the Q626 tool was moderate, with Cronbach's α of 0.723. The results indicated a significant improvement in Q626 scores for both the experimental group (EG) and the control group (CG) at T1 compared to T0 (p